Protocol for assessing and visualizing cell microaggregate formation in whole blood by imaging flow cytometry - Johannes Krell; Komal Kumar Javarappa; Angie Wenedy; Andrew L. Frelinger, III; Laurent Renia; Clarissa Prazeres da Costa; Martin Schlegel; Percy Knolle; Gerhard Schneider; Oliver Hayden (STAR Protocols)
Summary: Blood cell aggregates are clinically useful biomarkers in a number of medical disorders. This protocol provides accurate and quantitative analysis of cell aggregates using a small volume of whole blood and imaging flow cytometry. We describe steps for sample collection, staining, and measurement. We then detail gating procedures and analysis of cell morphology. Sample preparation artifacts, activation, and morphological changes of cells are mitigated by omitting erythrocyte lysis and leukocyte isolation while maintaining high-throughput accurate imaging of leukocytes and platelets. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.